Happily ever amish - Gray, Shelley Shepard (The Amish of Apple Creek, 2022)
"Addie Byler may be Apple Creek's resident wallflower, but she knows she has a lot to offer--and much to be grateful for. Raised by her loving grandmother, she lives a life filled with good friends and hard work. Wary of romance, Addie assumes no man will look beyond her glasses and her tendency to talk to her rescue donkey, Snickers--until the day she finds a note from a secret admirer. A prank, most likely. But then, a second note arrives. It's not that Daniel Miller doesn't like Addie, he just doesn't want to court her. She's too willful, too chatty, too odd. Yet when he learns she's been teased because she's never had a beau, he decides to send a little note of encouragement. One note leads to another. And when Addie begins replying with thoughtful messages of her own, he's struck by her sweetness and warmth. As chilly winter melts into spring, what began as a gesture of sympathy becomes something much deeper. Daniel fears revealing the truth, but with courage, faith--and a helping hand from their close-knit community--Apple Creek's most unlikely couple may find their path to happiness" --Provided by Publisher.